The regulation of immune cell trafficking by the extracellular matrix. (October 2015) - Hallmann, Rupert; Zhang, Xueli; Di Russo, Jacopo; Li, Lixia; Song, Jian; Hannocks, Melanie-Jane; Sorokin, Lydia
Abstract : The extracellular matrix (ECM) comes in different structural forms and biochemical compositions, which determine both its biophysical properties and its ability to convey specific signals to immune cells encountering or navigating through it. Traditionally, the role of the individual ECM molecules on cell migration has been investigated independent of considerations such as the tension/mechanical strength constituted by the ECM. However, more recently, this aspect has attracted considerable attention and data suggest that rigidity and molecular signals derived from the ECM define the mode of cell migration. We here review the different types of ECM encountered by migrating immune cells in vivo, as well as current information on how both molecular components of the ECM and their supramolecular structure can impact on modes of immune cell migration.